2010
DOI: 10.1097/jom.0b013e3181d44e3f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traffic-Related Outdoor Air Pollution on Respiratory Illness and Mortality in Children, Taking Into Account Indoor Air Pollution, in Indonesia

Abstract: Exposure to traffic-related outdoor air pollution would increase adverse health effects after adjusting for indoor air pollution. Furthermore, indoor air pollution could exacerbate the effects of outdoor air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…The study found urban children were at slightly higher risk of death than children from rural areas, which was similar to previous similar studies in Bangladesh and Indonesia [24, 25]; despite the fact that the majority of the households in rural Pakistan rely on solids fuels mainly due to the unavailability of better alternatives [44, 45]. An intervention study in Pakistan investigating indoor particulate matter (PM) concentrations in developing countries reported that PM was considerably higher in urban kitchens as rural kitchens were more ventilated than urban ones [46].…”
Section: Discussionsupporting
confidence: 91%
“…The study found urban children were at slightly higher risk of death than children from rural areas, which was similar to previous similar studies in Bangladesh and Indonesia [24, 25]; despite the fact that the majority of the households in rural Pakistan rely on solids fuels mainly due to the unavailability of better alternatives [44, 45]. An intervention study in Pakistan investigating indoor particulate matter (PM) concentrations in developing countries reported that PM was considerably higher in urban kitchens as rural kitchens were more ventilated than urban ones [46].…”
Section: Discussionsupporting
confidence: 91%
“…A total of 21 studies reported on non-fatal ALRI, without defining severity, including one RCT [24], 4 cross-sectional [25-28], 11 case-control [29-39] and 5 cohort studies [40-44], summarized by study design in Additional File 3, Table 1(a). The RCT by Hanna et al was not eligible as the outcome measures did not allow distinction of upper and lower respiratory infections [45].…”
Section: Resultsmentioning
confidence: 99%
“…Signs of sepsis and pneumonia in young babies are notoriously subtle and difficult to recognise,15 and so many studies of HAP exposure in neonates have focused on mortality rather than infection. With use of results from two studies, Bruce and colleagues16 calculated a pooled odds ratio (OR) of 1·14 (95% CI 0·87–1·48) for neonatal mortality in households using solid fuels;17,18 both studies included kerosene in the reference (clean fuel) group. Since then, Epstein and colleagues19 reported that neonatal death in India was strongly associated with household use of coal (18·54, 6·31–54·45) and might be associated with kerosene, but the OR for kerosene crosses the null, so the risk is not clear (2·30, 0·95–5·55).…”
Section: Respiratory Infectionsmentioning
confidence: 99%